A modified immune algorithm with spatial filtering for multiobjective topology optimisation of electromagnetic devices. Issue 3 (2014) - ,; ,; ,
Abstract : Purpose – In the development of electromagnetic devices, multiobjective topology optimisation is effective to obtain diverse design candidates for production models. However, multiobjective topology optimisation has not widely been performed because it is difficult to obtain resultant shapes for engineering realisation due to large search spaces. The purpose of this paper is to present a new multiobjective topology optimisation method.Design/methodology/approach – This paper presents a new multiobjective topology optimisation method in which the Immune Algorithm is modified for multiobjecrive optimisation and a shape modification process based on spatial filtering is employed.Findings – The present method shows that better Pareto solutions can be found in comparison with the conventional methods.Originality/value – A new effective multiobjective topology optimisation is presented. This method enables to diverse design candidates for production models.